Dynamic modelling of a proton exchange membrane (PEM) electrolyzer - Görgün, H (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
This paper describes a dynamic model for PEM electrolyzer based on conservation of mole balance at the anode and the cathode. A further feature of the model is it includes water phenomena, electro-osmotic drag and diffusion, through the membrane. The model considers PEM electrolyzer to be composed of four ancillaries: anode, cathode, membrane and voltage ancillary. Additionally, hydrogen storage dynamics is presented. The developed model is suitable for determining control strategy that will ensure efficient and reliable operation of the electrolyzer. Moreover, the dynamic model can be integrated with renewable energy systems models to design, analyze and optimize sustainable energy systems. The study illustrates the dynamic interactions within a PEM electrolyzer and shows the necessity of the proposed approach of separate ancillaries. (c) 2005 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: FUEL-CELL; SIMULATION; SYSTEM; Chemistry; Electrochemistry; Energy & Fuels